2012
DOI: 10.1021/ja308188z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the NAD(P)H Binding Site of Eukaryotic UDP-Galactopyranose Mutase

Abstract: UDP-galactopyranose mutase (UGM) plays an essential role in galactofuranose biosynthesis in microorganisms by catalyzing the conversion of UDP-galactopyranose to UDP-galactofuranose. The enzyme has gained attention recently as a promising target for the design of new antifungal, antitrypanosomal, and antileishmanial agents. Here we report the first crystal structure of UGM complexed with its redox partner NAD(P)H. Kinetic protein crystallography was used to obtain structures of oxidized Aspergillus fumigatus U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…37,45,51-53 Recently, two independent groups applied protein x-ray crystallography to determine the structure and investigate a potential biological reducing agent of the A. fumigatus UGM. 54-56 These studies revealed that despite differences in the prokaryotic and A. fumigatus genes, the overall structure and folds of prokaryotic and eukaryotic UGMs are similar. 54,55 Our ability to trap a catalytic intermediate (compound 2 ) further suggested that the active site of CeUGM is similar to that of its prokaryotic homologs.…”
Section: Resultsmentioning
confidence: 97%
“…37,45,51-53 Recently, two independent groups applied protein x-ray crystallography to determine the structure and investigate a potential biological reducing agent of the A. fumigatus UGM. 54-56 These studies revealed that despite differences in the prokaryotic and A. fumigatus genes, the overall structure and folds of prokaryotic and eukaryotic UGMs are similar. 54,55 Our ability to trap a catalytic intermediate (compound 2 ) further suggested that the active site of CeUGM is similar to that of its prokaryotic homologs.…”
Section: Resultsmentioning
confidence: 97%
“…2 -NADPH was synthesized by the method of Jeong and Gready (27) with some minor modifications as previously described (28). Briefly, 25 mg of NADP ϩ (5.6 mM final concentration), 480 l of 2-propanol-d8 (1 M final concentration), and 50 units of alcohol dehydrogenase (T. brockii) were added to 6 ml of 25 mM Tris-Cl, pH 9.0.…”
Section: Synthesis Of Deuterated Nadph-r-4hmentioning
confidence: 99%
“…Eukaryotic UGMs from the fungus A. fumigatus and from the parasites T. cruzi , L. mexicana , and L. infantum have been shown to utilize NADPH as a redox partner (Table 1) [30, 37, 38]. In addition, these enzymes can stabilize the reduced form of the flavin, even under aerobic conditions.…”
Section: Chemical Mechanisms Of Ugmmentioning
confidence: 99%
“…The rate of oxidation is 200–1500-fold slower than the reduction step, thus, the enzymes can turn over several hundred times before becoming oxidized (inactivated) [30, 38]. The structures of A. fumigatus UGM in complex with NADP(H) have recently been solved and a novel NADPH binding domain was identified [37]. Thus, at least for eUGMs, the mechanism of activation by NAD(P)H has been established.…”
Section: Chemical Mechanisms Of Ugmmentioning
confidence: 99%